Financial Market Development and Economic Growth. New or Old Nexus in the Euro Area? - Bukowski, Sławomir I.; Zięba, Łukasz J. (Central and Eastern European Economic Review, 2020)
The problems of the nexus of financial development, financial market development, and economic growth have so far been controversial. Some authors have questioned the linearity of that nexus or the general idea of nexus. In recent literature devoted to those problems, authors emphasise the changes in the link between financial development and economic growth. The consequences of financialization and the last financial crisis have become the premises for a new hypothesis concerning the nonlinearity of the financial development and economic growth nexus. Some authors indicate that this nexus probably has the shape of inverted letter U. When financialization measured by the relation of financial assets to GDP reaches too high a level, the impact of financial development on economic growth will be negative (after reaching the inflection point on the U curve). There are a number of arguments that indicate that the use of quadratic terms leads to statistical illusions, which are connected with specific mathematical and statistical features of the quadratic function form. Therefore, the authors have implemented the traditional method of the dynamic panel data model, which is unbalanced (because some of the data is not available). The aim of our research is to answer the question: does the nexus of financial market development and economic growth exist? Thus our hypothesis is as follows: financial market development influences economic growth in the euro area in an economically and statistically significant way. We investigate this phenomenon based on the euro area countries and implemented panel data models (unbalanced), and use annual data concerning main financial market development and macroeconomic control variables.